Effect of single dose cadmium chloride administration on oxidative stress in male and female rats - Kara, H; Karatas, F; Canatan, H (Tubitak Scientific & Technological Research Council Turkey, 2005)
This study was carried out to determine the effect of single dose cadmium chloride (CdCl2) administration on the possible development of oxidative stress by measuring malondialdehyde (MDA) levels in the liver, kidney and blood serum of male and female rats. For this purpose 80 animals (14-16 weeks old) were initially divided into two 2 groups according to sex, each containing 40 rats. Then both were divided into 5 equal treatment groups [0 (control) 0.5, 1, 2 and 4 mg/kg CdCl2 body weight by subcutanous injection, respectively]. The blood serum and tissues of the liver and kidney were collected after 24 h of treatment from anesthesized rats. MDA levels of the samples were determined by high performance liquid chromatography. Oxidative stress was evident in both sexes following 24 h exposure to all doses of CdCl2 compared to the controls. Liver MDA levels of male rats were higher than those of female ones. Although MDA levels in the serum and kidney of male rats were higher than those in females, these alterations were not statistically significant. In conclusion, these results show that cadmium causes early oxidative stress as demonstrated by increasee in MDA levels in the blood serum and liver and kidney tissues. In addition, the reason for the higher MDA level of in the liver of male rats compared with females could be due to differences in p450 dependent NADPH and higher levels of metallothionein in female rats.
Keywords: cadmium; malondialdehyde; oxidative stress; male and female rat